Effects of Slurry in Cu Chemical Mechanical Polishing (CMP) of TSVs for 3-D IC Integration - Jui-Chin Chen; Lau, J. H.; Pei-Jer Tzeng; Shang-Chun Chen; Chien-Ying Wu; Chien Chou Chen; Yu Chen Hsin; Yi-Feng Hsu; Shang Hung Shen; Sue-Chen Liao; Chi-Hon Ho; Cha-Hsin Lin; et al. (IEEE transactions on components, packaging, and manufacturing technology (2011), 2012)
In this paper, the optimization of Cu chemical-mechanical polishing (CMP) performance (dishing) for the removal of thick Cu-plating overburden due to Cu plating for deep through silicon via (TSV) in a 300-mm wafer is investigated. Moreover, backside isolation oxide CMP for TSV Cu exposure is examined. To obtain a minimum Cu dishing on the TSV region, a proper selection of Cu slurries is proposed for the current two-step Cu-polishing process. First, a bulk of Cu is removed with the slurry of high Cu removal rate and second, the Cu surface is planarized with the slurry of high Cu passivation capability. The Cu dishing can be improved up to 97% for the 10-μm-diameter TSVs on a 300-mm wafer. The dishing/erosion of the metal/oxide can be reduced with respect to a correspondingly optimized Cu-plating overburden for TSVs and redistribution layers. Cu metal dishing can be drastically reduced once the Cu overburdens are increased to a critical thickness. For backside isolation oxide CMP for TSV Cu exposure, the results show that the Cu studs of TSVs with a larger TSV diameter still keep in a plateau-like shape after CMP.